PENGUJIAN EFEK FLASH SALES DAN PROMOSI LIVE STREAMING TERHADAP MINAT BELI ONLINE MAHASISWA UNIVERSITAS SAMAWA - Purwadinata, Subhan; Kurniawan, Muhammad Fachrurrozy (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to determine the effect of flash sales and live streaming promotions on online buying interest among students at Samawa University, Sumbawa Besar. The type of this study was causal associative study used to examine the effect of flash sales and live streaming promotions on online buying interest among students at Samawa University, Sumbawa Besar. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents in this study were students from Samawa University, Sumbawa Besar who had made online purchases through the e-commerce TikTok shop, totaling 96 people who were determined using non-probability sampling techniques with the accidental sampling method. In this study, the data was processed using the SPSS program, to be studied and analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that flash sales and live streaming promotions had a positive and significant effect on online buying interest among students at Samawa University, Sumbawa Besar, either partially and simultaneously. The effect of flash sales and live streaming promotions on online buying interest among students at Samawa University, Sumbawa Besar was 25.5%, while the remaining of 74.5% was effected by other variables outside this research model, such as product quality, advertising and customer trust.